Contextualizing Teacher Education Emphases for Classroom Diversity - Kevin Murry; Cristina Fanning; Shabina Kavimandan (The Advocate, 2014)
Nominal attention has been dedicated to standards of best practice that local teachers should demonstrate in teaching culturally and linguistically diverse (CLD) students. The CREDE standards address the gap and emphasize five transnational, universals of best practice for CLD students/families. However, recent research indicates that teachers practices indicative of the most important of these, contextualization, are among the least robust of those observed. Necessarily, future research is needed to unpack these findings. In the interim, we argue that teachers’ critical reflection on their own socialization is essential to the fundamental understandings necessary for standards-based practices with these students and families.